2022
DOI: 10.3390/coatings12020235
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Squid Pen Chitosan Nanoparticles against Three Fungal Pathogens in Various Citrus Fruits In Vitro and In Vivo

Abstract: Fungal infections have been considered a primary cause of the postharvest losses of citrus fruits. Therefore, it is necessary to find low-cost and high antifungal activity materials for preventing the decay of citrus fruits after harvest. In this study, squid chitosan nanoparticles (SCNs) were prepared from squid pen chitosan and used as a biofungicide against three citrus fungal pathogens in both in vitro and in vivo evaluations. The prepared SCNs had a mean size of ca. 56 nm and a high zeta potential of +98.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This method, which is commonly called ionic gelation, allowed the preparation of CHNPs greater than 50 nm in diameter. For example, Cuong et al (2022) indicated that CHNPs synthesized by ionic gelation had a mean size of 56 nm (Figure 1a). Similarly, several reports described the synthesis of CHNPs with a size of 50−100 nm using the same procedure (Abdel-Rahman et al, 2021;Karimirad et al, 2019;Mohammadi et al, 2015a;Valizadeh et al, 2021).…”
Section: Preparation Of Chnpsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method, which is commonly called ionic gelation, allowed the preparation of CHNPs greater than 50 nm in diameter. For example, Cuong et al (2022) indicated that CHNPs synthesized by ionic gelation had a mean size of 56 nm (Figure 1a). Similarly, several reports described the synthesis of CHNPs with a size of 50−100 nm using the same procedure (Abdel-Rahman et al, 2021;Karimirad et al, 2019;Mohammadi et al, 2015a;Valizadeh et al, 2021).…”
Section: Preparation Of Chnpsmentioning
confidence: 99%
“…On the other F I G U R E 1 Shape and size of chitosan nanoparticles (CHNPs). (a) Transmission electron microscopy (TEM) images and size distribution of CHNPs synthesized using the ionic gelation method (Cuong et al, 2022). (b) Scanning electron microscopy (SEM) and TEM analyses of chitosan-phenylalanine NPs (Gohari et al, 2021).…”
Section: Preparation Of Chnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using as raw material chitin extracted from squid, Yusharani et al (2019) have obtained chitosan with a degree of deacetylation of 82-84%. With chitosan with a high degree of deacetylation, obtained from squid chitin, Cuong et al (2022) have formulated chitosan-tripolyphosphate nanomaterials, using chitosan, TPP, and acetic acid as raw materials. These nanomaterials were included in the culture medium in different concentrations (50ppm; 100ppm; 150ppm; 200ppm; 250ppm) and were tested on fungal phytopathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The best results were obtained for concentrations higher than 200 ppm, for microorganisms of the type A. alternata, P. digitatum and Lasiodiplodia sp. The mechanism of action was highlighted by SEM studies and showed that under the action of nanomaterials with chitosan, the plasma membrane of mycelia and spores is destroyed (Xing et al, 2009;Cuong et al, 2022). Taking into account the need to create pharmaceutical formulations in which the phenomenon of antibiotic resistance is completely eliminated, in the conducted study we proposed to test the antimicrobial activity of some biopreparations, made with biomolecules obtained from natural resources such as chitosan, collagen and reagents with the potential for use in regenerative medicine, respectively limonene and clotrimazole (Mohammed et al, 2022).…”
Section: Introductionmentioning
confidence: 99%